2020
DOI: 10.1016/j.bbamcr.2020.118805
|View full text |Cite
|
Sign up to set email alerts
|

The balancing act of NEET proteins: Iron, ROS, calcium and metabolism

Abstract: NEET proteins belong to a highly conserved group of [2Fe-2S] proteins found across all kingdoms of life. Due to their unique 2Fe-2S cluster structure, they play a key role in the regulation of many different redox and oxidation processes. In eukaryotes, NEET proteins are localized to the mitochondria, ER and the membranes connecting these organelles (MAM), and are involved in the control of multiple processes, ranging from autophagy and apoptosis to ferroptosis, oxidative stress, cell proliferation, redox cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
68
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 47 publications
(80 citation statements)
references
References 113 publications
(372 reference statements)
2
68
0
Order By: Relevance
“…Aside from NAF-1(−) induced changes in mitochondria-ER MAM integrity (Figures 2 and 3), the multiple changes observed in INS-1E cells upon NAF-1 suppression recapitulate what we and others have observed in previous studies with non-endocrine cells in culture and with animal models of WFS-T2 (i.e., knockouts of NAF-1) [15,[60][61][62]. The novel finding of this work is therefore the establishment of a causative association between NAF-1 repression that leads to a mitochondrial labile iron rise and an increased mROS formation that triggers ferroptosis, and the impairment of β-cell insulin secretion.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Aside from NAF-1(−) induced changes in mitochondria-ER MAM integrity (Figures 2 and 3), the multiple changes observed in INS-1E cells upon NAF-1 suppression recapitulate what we and others have observed in previous studies with non-endocrine cells in culture and with animal models of WFS-T2 (i.e., knockouts of NAF-1) [15,[60][61][62]. The novel finding of this work is therefore the establishment of a causative association between NAF-1 repression that leads to a mitochondrial labile iron rise and an increased mROS formation that triggers ferroptosis, and the impairment of β-cell insulin secretion.…”
Section: Discussionsupporting
confidence: 86%
“…Most of the mutations in the CISD2 gene, leading to WFS-T2, resulted in a complete or partial loss of the NAF-1 (Nutrient-deprivation Autophagy Factor-1) CISD2 protein, a protein that normally resides on the endoplasmic reticulum (ER), the outer mitochondrial membrane (OMM), and the mitochondria-ER-associated membranes (MAM) [ 12 ]. Interactome studies of NAF-1, a member of the [2Fe-2S] NEET protein family [ 13 ], implicated this protein in the regulation of autophagy and apoptosis, and added support to the empirical evidence associating NAF-1 with dysfunctional iron metabolism, ROS formation, and Ca 2+ signaling at the ER and mitochondria [ 13 , 14 , 15 ]. The association of NAF-1 function with altered iron and ROS metabolism gained further support from studies conducted in cancer cells [ 14 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…We speculate that such differences may reflect their distinct biological functions; notably in the pancreas, a high level of CISD2 expression is accompanied by a low level of mitoNEET. Since both proteins are involved in the regulation of mitochondrial calcium stores through distinct mechanisms [ 27 ], the relative dependence of pancreatic cells on CISD2 for this essential regulation might help to understand why CISD2 deficiency in WFS2 patients leads to an early dysfunction of this tissue and diabetes. A similar expression profile in the spleen, where CISD2 also predominates over mitoNEET, suggests an as yet unanticipated possible involvement of CISD2 in immune cells.…”
Section: Discussionmentioning
confidence: 99%
“…These studies indicate that oxidative stress is closely associated with both apoptosis and ferroptosis in cells. It has been indicated that ferroptosis is involved in the pathological mechanisms of numerous diseases, including diabetes, neurodegenerative diseases, atherosclerosis, obesity, non-alcoholic fatty liver disease and types of cancer ( 58 ). Notably, ferroptosis-related pathophysiological changes are also observed in DN ( 18 , 19 ).…”
Section: Discussionmentioning
confidence: 99%